A Study on The Innovative Pathways for Integrating Craftsmanship Spirit and Ideological-Political Education in Vocational Education - Liu, Xiang; Jiang, Jiaxiang; Huang, Jiayao (Pacific International Journal, 2024)
This study explores innovative pathways to integrate craftsmanship spirit with ideological-political education within vocational education settings, using Jingdezhen Vocational University of Art as a case study. Craftsmanship spirit, deeply rooted in Chinese culture, emphasizes values such as dedication, innovation, and the pursuit of excellence. Its integration into ideological-political education enhances vocational training by fostering ethical responsibility, societal contribution, and professional competence. Through qualitative research involving interviews with faculty and students, as well as campus observations, this study identifies challenges, successes, and actionable strategies for optimizing curriculum design, teaching practices, and institutional collaboration. Key findings highlight the potential of hands-on learning, interdisciplinary projects, and cultural activities to deepen this integration. Recommendations include curriculum innovation, faculty development, enhanced practical environments, and leveraging digital tools. This study offers a replicable framework for vocational institutions seeking to balance technical expertise with ethical and societal values in the modern workforce.